We could have saved him - Kumar, Manish (Research and Humanities in Medical Education, 2020)
Violence against doctors is a global phenomenon but, in India, the situation is grim. News of violence against medical professionals is published with an alarming regularity, to the point where it has become "part of the package" of being a healthcare worker. Most of these untoward incidents are in the emotionally charged environs of the emergency room where provision of healthcare is abysmally unstructured. Many recent incidents have snowballed into controversies attracting national and international headlines. Disillusionment in the young professionals is palpable, yet, when the media spotlight moves elsewhere, not many amongst us reflect on how these incidents have changed the lives of those impacted. This story is a fictionalized account of incidents in a medical college after a stampede during a festival. The story will resonate across different settings where medical professionals have faced the brunt of failures of our healthcare system. Most of us have survived with physical and psychological scars, while a few others have quit the system altogether.